2011
DOI: 10.5014/ajot.2011.002063
|View full text |Cite
|
Sign up to set email alerts
|

Modified Constraint-Induced Movement Therapy for Elderly Clients With Subacute Stroke

Abstract: A growing body of research, including evidence from numerous randomized controlled trials, suggests that constraint-induced movement therapy (CIMT) reduces impairment. The mean age of participants in most studies has been <65 yr, even though most stroke survivors are older than that. We investigated the efficacy of a modified CIMT protocol on participation, activity, and impairment in a population of older adults experiencing subacute stroke. Using an interrupted time series design, 4 older adults (mean age 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…A Socially Assistive Robot (SAR) can be integrated into the rehabilitation process to provide motivation and support through social interaction for at-home or self-directed in-clinic rehabilitation exercises between visits to an occupational or physical therapist. In order to provide this type of support with a SAR, a greater understanding of how to motivate a patient is needed, since in the majority of rehabilitation paradigms (e.g., constraint induced movement therapy), it is a critical element of the intervention [2], [3]. Self-efficacy, a person's perception of their own competence at a task, is related to motivation, is thought to mediate motor performance, and may underlie many facets of post-stroke outcomes, including lower extremity performance, balance, and health outcomes [4], [5], [6], as well as upper-extremity limb choice [7], [8].…”
Section: Introductionmentioning
confidence: 99%
“…A Socially Assistive Robot (SAR) can be integrated into the rehabilitation process to provide motivation and support through social interaction for at-home or self-directed in-clinic rehabilitation exercises between visits to an occupational or physical therapist. In order to provide this type of support with a SAR, a greater understanding of how to motivate a patient is needed, since in the majority of rehabilitation paradigms (e.g., constraint induced movement therapy), it is a critical element of the intervention [2], [3]. Self-efficacy, a person's perception of their own competence at a task, is related to motivation, is thought to mediate motor performance, and may underlie many facets of post-stroke outcomes, including lower extremity performance, balance, and health outcomes [4], [5], [6], as well as upper-extremity limb choice [7], [8].…”
Section: Introductionmentioning
confidence: 99%
“…17 Furthermore, McCall and colleagues found that, in people with subacute stroke, a modified form of CIMT led to clinically meaningful changes in CAHAI score (i.e., a mean change score >6.3 as determined by Barreca and colleagues 21 ). 24 One participant in their study who presented with CAHAI and CMSA baseline scores similar to those of PF, achieved a change in score of 12.8 points on the CAHAI. 24 Based on PF's initial presentation and existing evidence, we are guardedly optimistic that PF can achieve better function and more spontaneous use of his paretic UE.…”
Section: The Evidencementioning
confidence: 87%
“…24 One participant in their study who presented with CAHAI and CMSA baseline scores similar to those of PF, achieved a change in score of 12.8 points on the CAHAI. 24 Based on PF's initial presentation and existing evidence, we are guardedly optimistic that PF can achieve better function and more spontaneous use of his paretic UE. The fact that PF does not have shoulder pain is an asset, as shoulder pain has been shown to hinder recovery after stroke.…”
Section: The Evidencementioning
confidence: 87%
“…The fourth CIMT study questioned whether CIMT could produce similar outcomes when compared with intensitymatched bilateral UE treatment; interestingly, both groups made notable gains in Wolf Motor Function Test and Canadian Occupational Performance Measure (COPM) scores, but no significant group differences were found (Hayner et al, 2010). A modified CIMT protocol was implemented to assess changes in participation, activity, and UE impairment in four older people with subacute stroke (McCall et al, 2011), and the final study paired CIMT with eye patching to assess changes in functional skills, eye movement, and trunk-arm kinematics (Wu et al, 2013). Motor learn-ing, another established area of study, was examined by Giuffrida et al (2009).…”
Section: Descriptive; Anovasmentioning
confidence: 99%